2003
DOI: 10.1080/09571260410001677969
|View full text |Cite
|
Sign up to set email alerts
|

The nose knows: influence of colour on perception of wine aroma

Abstract: The mental processes that enable a wine connoisseur to identify a favourite vintage have received little systematic study. Two experiments explored wine expertise by investigating perceptual processing in judgements of wine aroma. Specifically, we investigated olfactory perceptual bias, a cognitive construct concerned with how what we already know influences what we smell. Colour-induced olfactory bias was investigated in wine experts (Experiment 1) and in social drinkers (Experiment 2). We hypothesised that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 28 publications
10
84
1
Order By: Relevance
“…Indeed, previous works have shown that as expertise increases, the organization of chemosensory knowledge changes (Solomon 1997;Ballester et al 2008). In line with this idea, Parr et al (2003) investigated the occurrence of color-induced olfactory bias in wine experts and in novices. The authors hypothesized that because of their knowledgedriven expectations, experts should be more prone to experience a color-induced olfactory bias than novices.…”
Section: Introductionmentioning
confidence: 66%
“…Indeed, previous works have shown that as expertise increases, the organization of chemosensory knowledge changes (Solomon 1997;Ballester et al 2008). In line with this idea, Parr et al (2003) investigated the occurrence of color-induced olfactory bias in wine experts and in novices. The authors hypothesized that because of their knowledgedriven expectations, experts should be more prone to experience a color-induced olfactory bias than novices.…”
Section: Introductionmentioning
confidence: 66%
“…Given that blind tasting is a typical methodological approach in the context of food and beverage marketing, our experimental design relies on existing studies in the field of wine marketing (e.g. Ballester et al, 2005;Lecocq et al, 2005;Masson et al, 2008;Parr et al, 2003;Solomon, 1997;Wansink, 2006). Particularly, our blind tests were designed to measure the extent to which the "organic" status brings bias into the sensory perception and evaluation of the given wines.…”
Section: Rq4 Is There Any Association Between Positive Attitudes Towmentioning
confidence: 99%
“…When we evaluate a wine, even at the level of a simple recognition judgment, processing the multi-sensorial input likely involves all of the processes mentioned above under most circumstances. One important aspect of cognitive processing in a wine-tasting context is the integration of 'top-down' and 'bottom-up' information processes (Parr, White & Heatherbell, 2003). This involves a taster's already-gained knowledge and emotions influencing perception of…”
Section: A Cognitive Analysis Of Wine Tastingmentioning
confidence: 99%
“…This includes work on colour-flavour perceptual bias (Morrot et al, 2001;Parr et al, 2003) and other expectation-driven phenomena such as influence of wine price or bottle weight (Piqueras-Fiszman & Spence, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%